Modern Application and Demonstration of the Ancient Rhetorical Exercises „Encomium“ and „Etopeya“ - Ivancheva, Adriana (Media and Language, 2020)
This report aims to introduce to the audience the practical application of the ancient rhetorical exercises of encomium and ethopeya, which are an important part of a speaker’s training and education, a way to upgrade his personality, to acquire specific and essential qualities that are fundamental for every successful speaker. These rhetorical exercises are of great use to this day in the media and in other spheres of society, which are a practical and creative tool for shaping a orator’s speech, putting it into practice in front of an audience, developing particularly key rhetorical skills, and helping the personality of the speaker to grow up.